The Anarchist’s Jukebox?: A Historical Account of the File Sharing Conflict - Hill, Christopher (Auckland University of Technology, 2005)
This thesis explores the impact of file sharing on the established United States music industry from 1999 to 2005.The file sharing debate is essentially a conflict between the media/music conglomerates and those who exchange music through cyberspace. To understand the dynamics of this conflict, it is necessary to examine the historical context of the music industry and digital convergence. The File sharing debate exemplifies conflict between an industry and uses of new technology, as well as a conflict over the future distribution and communication of information. The framing of the debate within the mainstream media has cast file sharing as an illegal disruption of the established music industry and of the evolution of music. I will argue that this representation obscures the interests and principles at stake. File sharing represents a cultural and technological alternative to established systems of music copyright. In this context the new forms of music potentially undermine the media/music conglomerates control over production and distribution. I will outline how the music industry has attempted to control the major file sharing networks to prevent new competition and to curb any further technological developments which might challenge the industrial structure of digital music distribution. I will discuss the political, economic and social cost of this strategy for music. I argue that the established industry has been the real disruption to the evolution and proliferation of music. It is this author’s view that the emergence of file sharing, as a counter public sphere, between 1999 and 2005 has instituted a number of significant changes to the structure of the music industry which have been important for the evolution of music. However file sharing is now at a point of transition in its relationship to the music industry, file sharing may well be incorporated within the music industry’s strategic objectives.
Keywords: Music trade; Sound recording industry; Peer-to-peer architecture (Computer networks) Copyright -- Music -- United States